(untitled) (International Journal of Financial, Administrative and Economic Sciences, 2025)
This study aimed to analyze the structure of public revenues in Iraq during the period (2015-2020) in order to show the financial sources that make up those revenues and to determine the factors affecting the contribution of those sources. In the structure of tax revenues based on oil revenues, which are characterized by instability and stability in financing the general budget, and the weak contribution of other sources of financing, the most important of which are taxes). Vulnerable to shocks, especially external ones, whether represented by a drop in the world oil price or a decrease in global demand for oil, and the dangerous repercussions of this on the financing of the state’s general budget, and consequently on the overall economic and social life in the country. Finally, the study presented a number of recommendations that could contribute to diversifying the sources of public revenue and activating the financing role of non-oil sources in the Iraqi economy, the most important of which are taxes.